Analysis of the Competitive Advantage of Madura Stores in Business Competition in the Horseshoe Region: A Review of Islamic Business Ethics - Ainol Yaqin; Oktavia Nur Safitri; Azizi Abu Bakar (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The dynamics of retail competition in Indonesia showcase the unique resilience of traditional businesses, one of which is Toko Madura. This study aims to analyze in depth how the application of Islamic business ethics values ​​creates a competitive advantage for Toko Madura in facing competition, particularly in the Tapal Kuda area, East Java. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation studies. The results reveal that Toko Madura's competitive advantage stems from the internalization and implementation of Islamic ethical values ​​such as shiddiq (honesty), amanah (responsibility), 'adl (justice), and ta'āwun (mutual assistance) in its business operations. These values ​​are manifested in an interest-free credit system (lending), close kinship relationships with customers, flexible operating hours, and adaptation to the socio-economic conditions of the local community. The application of these values ​​not only builds strong customer loyalty and trust but also serves as a key factor in business resilience amidst the onslaught of modern retail. This study concludes that the integration of sharia principles and the local wisdom of Pendalungan culture creates a sustainable and competitive business model. The findings are expected to serve as a strategic foundation for the development of values-based MSMEs and contribute academically to more contextual studies of sharia economics.